Manajemen Berbasis Masyarakat dalam Pengelolaan Lembaga Pendidikan Anak Usia Dini - Muhammad Alim Kahfi (Lembaga Sosial Rumah Indonesia, 2022)
This study aims to describe the basic concepts of community-based education management both theoretically and practically and explain how community-based management is implemented in the management of early childhood education institutions. This study uses a type of library research (library research). The results of the study show that there are at least eight types of community that play a role in community-based management in PAUD management, including individuals (religious leaders), families, Education Implementation Support Agencies (BP3) or school committees, professional organizations (GOPTKI, IGTKI, IGPAUD), entrepreneurs, community organizations, quality control of educational services, non-governmental organizations (NGOs).